The amerindian heterotopia and the resistance against the Brazilian ethnocide - Silva, Gustavo Ruiz da (Universidade Estadual de Campinas, 2022)
This article aims, starting from a contemporary problem (the destruction of indigenous lives and cultures in Brazil), to think about ethical questions – especially in what concerns other ways of constituting subjectivity and (dis)obedience. Thus, the indigenous obedience issue will be based on Pierre Clastres’ societies against the State, giving an extent to Viveiros de Castros and possible relationships with our western reality. The subjectivity issue, then, will be approached based on what was pointed out to us by Michel Foucault. Facing these Amerindian realities as heterotopias, how could we produce resistances and dissonant possibilities in our present reality?